Speech text of networking dinner international conference on public policy and social sciences (ICoPS) 2023 / Prof. Datuk Ts. Dr. Roziah Mohd Janor - Mohd Janor, Roziah (2023)
It is with great pleasure that I welcome everyone to the International Conference on Public Policy and Social Sciences (ICoPS) 2023 Dinner Event.